2002
DOI: 10.1107/s0907444902005322
|View full text |Cite
|
Sign up to set email alerts
|

Protein crystallization for genomics: towards high-throughput optimization techniques

Abstract: Protein crystallization has gained a new strategic and commercial relevance in the next phase of the genome projects, in which X‐ray crystallography will play a major role. Considerable advances have been made in the automation of protein preparation and also in the X‐ray analysis and bioinformatics stages once diffraction‐quality crystals are available. These advances have not yet been matched by equally good methods for the crystallization process itself. In the area of crystallization, the main effort and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…Studies on biocatalysis showed that some imidazolium-based ILs could enhance protein activity and make it more stable [21]. In 2002, scientists found gel media, in some way mimicking a microgravity environment, could reduce density driven convection and sedimentation, which resulted in a significant improvement of crystal order [22,23]. Chayen [24,25] reported that paraffin and silicone oils could prevent the evaporation of small-volume microbatch trials.…”
Section: Introductionmentioning
confidence: 98%
“…Studies on biocatalysis showed that some imidazolium-based ILs could enhance protein activity and make it more stable [21]. In 2002, scientists found gel media, in some way mimicking a microgravity environment, could reduce density driven convection and sedimentation, which resulted in a significant improvement of crystal order [22,23]. Chayen [24,25] reported that paraffin and silicone oils could prevent the evaporation of small-volume microbatch trials.…”
Section: Introductionmentioning
confidence: 98%
“…Although efforts to automate crystal optimization are now underway [1], a follow-up optimization experiment is often still designed and implemented manually. Microseeding, and especially streak seeding, are easy to perform which makes them attractive as optimization methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, screening in itself, no matter how extensive, is still no guarantee that crystals will be found or that they will provide diffraction-quality data. At least half of the crystals obtained in an initial screen cannot be used without further optimization [1]. Therefore, optimization methods are often crucial for the success of a crystallization project.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization using micro-bubble Generally, one of the conventional protein crystallization methods is hanging drop method and sitting drop method which use supersaturation of the protein solution and classified as vapor diffusion [6][7] In case of the method, a drop composed of protein and regent is placed in the arrayed well chamber with reservoir solution. Typically, the drop contains a lower reagent concentration than that of the reservoir solution.…”
Section: Introduction Protein Conformationmentioning
confidence: 99%